Pola Interaksi Wilayah Perkotaan dan Pedesaan Dalam Pemenuhan Kebutuhan Ekonomi Masyarakat - Tia Setiawati; Siti Fadjarajani (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
The interaction between urban and rural areas is a crucial phenomenon in the dynamics of meeting people’s economic needs, particularly amidst increasingly complex spatial structure changes and social mobility. This study aims to examine the patterns of reciprocal relationships between cities and villages in the context of resource distribution, market access, and labor flows that influence people’s economic well-being. Using literature review and qualitative descriptive analysis, data were reviewed from various academic sources and regional development policies. The results show that urban areas act as centers of consumption and distribution, while rural areas provide commodities and labor, forming interdependent and dynamic interaction patterns. These findings emphasize the importance of integrated regional planning to create economic balance and equitable access between regions.